External locus-of-hope, well-being, and coping of students: A cross-cultural examination within Asia - Bernardo, Allan B. I. (Wiley-Liss Inc., 2018)
Intervention programs to strengthen hope in students have been developed and implemented in schools. The programs are based on Snyder's theory that defines hope as thoughts regarding personal capacities and pathways for goal attainment. Hope theory was recently extended to include external loci-of-hope, which derive from conjoint models of agency emphasized in collectivist societies. But evidence on external loci-of-hope's positive influence on students’ well-being is limited. Two studies (involving student samples from four universities in Asian cities) explored how external loci-of-hope relate to students’ life satisfaction, personal well-being (self-esteem, self-mastery), relational well-being (relational self-esteem, communal mastery), and coping styles for school-related stress. Results show that external loci-of-hope dimensions predict students’ life satisfaction and relational aspects of well-being, but also predict maladaptive coping. The results are discussed in relation to how the work of psychologists in schools benefit from approaches that contextualize theoretical precepts in cultural meanings and experiences in different parts of the world.